Legume proteins as sustainable alternative proteins: composition, processing modifications, functional properties, and therapeutic potential in women’s health amid global protein shortage - Huijie Wu; Shaotao Jiang; Lewei Tu; Miao Dong; Lixian Wu; Yan Ai; Ying Liang; Ye Peng; Quancai Sun; Ying Xiao (Critical Reviews in Food Science and Nutrition, 2026)

Impact of Industrial Agglomeration on Environmental Efficiency of China’s Major Freshwater Aquaculture Regions - Qiansheng Wan; Yingli Zhang; Shunxiang Yang; Lewei Peng (Fishes, 2026)
Freshwater aquaculture in China has expanded rapidly in recent decades, raising growing concerns about its environmental sustainability. However, the relationship between industrial agglomeration and environmental efficiency in freshwater aquaculture remains insufficiently understood. Using panel data from 18 major freshwater aquaculture provinces in China from 2009 to 2023, this study investigates the nonlinear effects of industrial agglomeration on environmental efficiency. Environmental efficiency is evaluated using a Global Super-SBM model incorporating undesirable outputs, while industrial agglomeration is measured by the location quotient index. A two-way fixed-effects model is employed for empirical estimation. The results reveal a significant inverted U-shaped relationship between industrial agglomeration and environmental efficiency, with a turning point at an agglomeration level of 2.519. Moderate agglomeration improves environmental efficiency through economies of scale and technology diffusion, whereas excessive agglomeration generates crowding effects that reduce efficiency. Further mechanism analysis shows that technology diffusion, proxied by the number of trained fishermen, plays a significant mediating role in this relationship. This study provides new empirical evidence on the nonlinear environmental effects of industrial agglomeration in freshwater aquaculture and offers policy implications for optimizing industrial spatial layout and developing differentiated environmental regulations to support the green and sustainable development of the sector.

Measurement and Analysis of Influencing Factors of Green Total Factor Productivity in Mariculture: Empirical Evidence from China - Lewei Peng; Ying Ma; Linhua Peng; Zhoufu Yan; Lixia Zhang (Fishes, 2026)
Enhancing mariculture’s green total factor productivity (GTFP) is essential to balance industrial growth with ecology, safeguard global food security, and meet UN Sustainable Development Goal 14 amid mounting marine stress. As a global leading mariculture producer, China provides a typical research sample. This study constructs a mariculture GTFP measurement index system, estimates GTFP in China’s coastal provinces via the global Super-SBM model, identifies root causes of efficiency loss, and explores influencing factors and spatial spillover effects using a spatial econometric model. The results show that the overall mariculture GTFP of China’s coastal provinces exhibits a fluctuating upward trend with significant regional heterogeneity, specifically presenting a distribution pattern of “the highest in the South China Sea Region, followed by the East China Sea Region, and the lowest in the Yellow Sea and Bohai Sea Region”. Meanwhile, mariculture GTFP shows significant positive spatial autocorrelation, with distinct High-High and Low-Low agglomeration characteristics. Excessive resource consumption and undesirable output discharge are the core drivers of efficiency loss. For direct effects, industrial scale, industrial structure, fishermen’s income, transportation accessibility, internet development, technology adoption, and environmental regulation significantly boost local GTFP, while fishery disasters exert a significant negative impact. For spatial spillovers, industrial scale, industrial structure, and internet development show significant positive effects, while fishermen’s income and urbanization present negative effects. Based on these findings, this study proposes targeted multi-stakeholder optimization paths, providing decision support for China’s mariculture green development and replicable experience for global coastal countries.

Serum hepcidin, iron stores, and iron availability are associated with cardiovascular health in Chinese children and adolescents: Basing on Life’s Essential 8 metrics - Yueqin Zhou; Tianze Li; Lewei Zhu; Zhijun Lu; Wei Peng; Youdan Hu; Jiawang Liu; Jialin Yuan; Yanna Zhu (Journal of Trace Elements in Medicine and Biology, 2026)

Low-velocity impact response of bio-inspired multi-sinusoidal corrugated sandwich structure - Jing Sun; Honghui Li; Haikun Peng; Chao Ding; Lewei Yan; Xinmei Xiang (Engineering Structures, 2026)

Dynamic coupling between cementation and porosity evolution of the Chang 8 tight sandstone reservoir, Ordos Basin: Insights from in-situ microanalysis - Ruiliang Guo; Weiwei Yang; Xiuqin Deng; Shuting Shi; Shutong Li; Junli Qiu; Jiaqiang Zhang; Junlin Chen; Lewei Hao; Xiaofeng Ma; Dongxu Ma; Peng Liu (Marine and Petroleum Geology, 2024)

The burgeoning importance of PIWI-interacting RNAs in cancer progression - Xinpei Deng; Tianle Liao; Jindong Xie; Da Kang; Yiwei He; Yuying Sun; Zhangling Wang; Yongluo Jiang; Xuan Miao; Yixuan Yan; Hailin Tang; Lewei Zhu; et al. (Science China Life Sciences, 2024)

Influencing factors of bioaugmentation treatment of PAH-contaminated soils in slurry bioreactors - Shiyu Bao; Likun Zhao; Yuanwen Liu; Lewei Yang; Peng Liu; Chaoqi Chen; Xuhui Mao (Journal of Environmental Chemical Engineering, 2023)